CT and DSA for evaluation of spontaneous intracerebral lobar bleedings - Altenbernd, Jens-Christian; Fischer, Sebastian; Scharbrodt, Wolfram; Schimrigk, Sebastian; Eyding, Jens; Nordmeyer, Hannes; Wohlert, Christine; Dörner, Nils; Li, Yan; Wrede, Karsten; Pierscianek, Daniela; Köhrmann, Martin; et al. (Frontiers in Neurology, 2022)
Purpose This study retrospectively examined the extent to which computed tomography angiography (CTA) and digital subtraction angiography (DSA) can help identify the cause of lobar intracerebral bleeding. Materials and methods In the period from 2002 to 2020, data from patients who were >18 years at a university and an academic teaching hospital with lobar intracerebral bleeding were evaluated retrospectively. The CTA DSA data were reviewed separately by two neuroradiologists, and differences in opinion were resolved by consensus after discussion. A positive finding was defined as an underlying vascular etiology of lobar bleeding. Results The data of 412 patients were retrospectively investigated. DSA detected a macrovascular cause of bleeding in 125/412 patients (33%). In total, sixty patients had AVMs (15%), 30 patients with aneurysms (7%), 12 patients with vasculitis (3%), and 23 patients with dural fistulas (6%). The sensitivity, specificity, positive and negative predictive values, and accuracy of CTA compared with DSA were 93, 97, 100, and 97%. There were false-negative CTA readings for two AVMs and one dural fistula. Conclusion The DSA is still the gold standard diagnostic modality for detecting macrovascular causes of ICH; however, most patients with lobar ICH can be investigated first with CTA, and the cause of bleeding can be found. Our results showed higher sensitivity and specificity than those of other CTA studies.